KONCEPT INTELEKTUANOG KAPITALA -TEORIJSKI DOPRINOS UPRAVLJAČKOJ TEORIJI PREDUZEĆA - Komnenić, Biserka; Pulić, Ante (International Journal of Economic Practice and Policy, 2022)
Given that the concept of Intellectual capital (IC) came from business practice,  it can be said that it is a practice in search of a theory. Studying the theoretical contribution of this concept is challenging as it demands the systematization of all relevant theories in which it finds its foundation and all aspects of its research. The crucial issues addressed in the concept of IC are: Has the economy based on knowledge influenced the emergence of a new matrix of value creation, and, if so, how is it possible to identify the essential resources which have the most influence on the process of value creation? To answer these questions, the concept of IC develops both the theoretical basis and practical guidelines and tools that contribute to a more precise definition of the strategic assets of the firm and their role in the process of value creation. For the concept of intellectual capital, the articulation of the value creation process is the essential precondition for firms’ success because that is something intrinsic to the firm and cannot be imitated by competitors.  This study aims to determine the contribution of the IC concept to the managerial theories of the firm.
Keywords: intellectual capital; theory of the firm; core capabilities; strategic resources; value creation